# Class 7 Mathematics / Integers / Model Questions

CBSE Class 7 Mathematics/ Integers is designed for Class 7 Mathematics students. Here you can find out model questions from the chapter Integers.

CBSE Class 7 Mathematics/ Integers – Chapter 1/ Model Questions
Total: 25 Marks Time: 45 minutes
I. Fill in the blanks (1 mark)

1. (-4) x (-3) = ———-
2. ———- is the additive identity for integers.
II. Answer the following (2 marks)
3. Find
i) (-25) x 0 x 4
ii) (-1) x (-1) x (-1)
4. Evaluate:
i) (-20) / (-4)
ii) (-50) / 10
5. Write the properties used here:
i) (-3) x 5 = 5 x (-3)
ii) (-4) x [(3) x (-2)] = [(-4) x 3] x (-2)
III. Answer the following (3 marks)
6. Verify that (-3) x [2 + (-6)] = (-3) x 2 + (-3) x (-6)
7. Find the product using suitable properties
i) 55 x (-35) + (-35) x (-45)
ii) 25 x (-24) x 4
8. Fill in the blanks:
i) 25 / —- = -1
ii) (-75) /75 = —–
iii) (-12) / —- = -3
9. Find
i) (-10) + (-2)
ii) 22 – (-20)
iii) (-100) – (-100)
IV. Answer the following: (5 marks)
10. Use appropriate symbols <,>, =
i) (-3) + (-4) —– (-1) + (-6)
ii) 2 x (-5) —— (-1) x (-4)
iii) 4 – (-6) —– 3 – (-3)
iv) 4 x 0 —– (-1) x (-4)
v) (-1) x (-1) —– (-1) x (-1) x (-1)

I. Fill in the blanks (1 mark)

1. 12
2. 0
II. Answer the following (2 marks)
3. i) 0
ii) -1
4. i) 5
ii) -5
5. i) Commutative property
ii) Associative property
III. Answer the following (3 marks)
6. LHS = (-3) x [2 + (-6)] = (-3) x (-4) = 12
RHS = (-3) x 2 + (-3) x (-6) = (-6) + 18 = 12
Here LHS = RHS. So verified.
7. i) 55 x (-35) + (-35) x (-45) = (-35) [55 + (-45)] = (-35) x 10 = -350
ii) 25 x (-24) x 4 = (25 x 4) (-24) = 100 x (-24) = -240
8. i) 25/ (-25) = -1
ii) (-75) /75 = -1
iii) (-12)/4 = -3
9. i) (-10) + (-2) = -12
ii) 22 – (-20) = 22 + 20 = 42
iii) (-100) – (-100) = -100 + 100 = 0
IV. Answer the following (5 marks)
10. i) (-3) + (-4) = -7, (-1) + (-6) = -7
So (-3) + (-4) = (-1) + (-6)
ii) 2 x (-5) = -10, (-1) x (-4) = 4
So 2 x (-5) < (-1) x (-4) iii) 4 – (-6) = 4 + 6 = 10, 3 – (-3) = 3 + 3 = 9 So 4 – (-6) > 3 – (-3)
iv) 4 x 0 = 0, (-1) x (-4) = 4
So 4 x 0 < (-1) x (-4) v) (-1) x (-1) = 1, (-1) x (-1) x (-1) = -1 So (-1) x (-1) > (-1) x (-1) x (-1)